(untitled) (College of Basic Education Research Journal, 2025)
Capital Plays important role in important issues enlisted within specific additions and principles like - increasing and doubling productivity. You can start your own business without having capital for it, and this is necessary if you choose to increase your productivity and obtain multiple products that you provide. Capital’s role became larger and more important, specially within great advances in technology . Goods that can be produced manually over a long period are now produced many times more in a short period through use of specialized equipment and machines. Capital provides equipment and raw materials for manufacturing. Capital With aim of providing necessary raw materials for production in good quality and sufficient quantity, it also provides necessary equipment and devices that facilitate production process, without which it would be impossible to improve and increase productivity.